Design of a Web-Based Salary Management Information System Using the Zachman Framework: A Case Study of Batu City Government - Sabirina Ayu, Estrielita; Abdul Rahman, Maulana (International Journal of Multidisciplinary Applied and Science Research, 2025)
Efficient salary management is crucial for ensuring transparency and accountability in government institutions. The Batu City Government currently faces challenges with its desktop-based salary management system, which is prone to delays, errors, and limited transparency. This study aims to design a web-based salary management information system using the Zachman Framework to address these issues. A qualitative research method with a case study approach was applied, focusing on the Batu City Government. The Zachman Framework was utilized to ensure that all perspectives of the system—from planning and user needs to technical design—were considered in the development process. The findings reveal that the proposed web-based system significantly improves efficiency by automating salary calculations, enhances transparency by providing real-time access to salary information, and simplifies monthly report generation. Furthermore, the system incorporates robust security features to protect sensitive employee data. The study concludes that the web-based salary management system, designed using the Zachman Framework, offers an effective solution for the Batu City Government, providing a more efficient, accurate, and transparent approach to salary management. The implementation of this system can serve as a model for other government institutions seeking to modernize their administrative processes.